Water in dry regions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An international scientific conference on the hydrology in Mediterranean and semi-arid regions will be held from 4 to 10 April 2003 in Montpellier, France. It will address the hydrological effects of climate change and seasonal fluctuations,...